Wetlands: conservation's poor cousins - Kingsford, Richard T.; Basset, Alberto; Jackson, Leland (Aquatic conservation, 2016)
About 5–10% of the world's land surface is currently wetland but possibly >70% is already destroyed or impaired. Conservation of these unique ecosystems lags progress in other realms, reflected in high rates of biodiversity loss. Wetlands provide a range of critically important ecosystem services including fresh water, nutrient cycling, food and fibre production, carbon fixation and storage, flood mitigation and water storage; water treatment and purification and habitats for biodiversity. There is increasing recognition that these services provide real economic values. Wetlands are affected by numerous threats including habitat loss and degradation, climate change, pollution, invasive species, overharvesting and disease. The most serious impact is from habitat loss and degradation caused by upstream water resource developments and conversion to agriculture, industry and transport, and urban development. The status of the distribution and extent of the world's wetlands remains poorly known, varying among countries. Wetland loss has varied internationally, with generally higher impacts in the Northern Hemisphere, with its long history of conversion to urban centres, ports and agriculture and yet there are increasing losses occurring in developing continents in the south. Wetland conservation needs to focus primarily on identification of priority areas for biodiversity conservation and legal protection, including Ramsar‐listing. Identification of wetland biodiversity hotspots for conservation should be an imperative, with associated Ramsar‐listing. There also needs to be effective protection of flow regimes. Mitigation of other deleterious processes, pollution, overharvesting, invasive species and disease, also remains particularly important. Conservation of wetlands remains especially challenging, given the importance of fresh water for human communities, industry and agriculture. Without effective conservation actions, mitigation of threats, rigorous risk assessment and acknowledgement of the value of wetland ecosystem services, wetland conservation will continue to lag behind conservation in other realms in protecting the Earth's biodiversity. Copyright © 2016 John Wiley & Sons, Ltd.